Length-weight relationship and condition factors of Lepturacanthus savala in Lampung Bay, Indonesia - DAVID JULIAN; MUHAMMAD REZA; MUHAMAD GILANG ARINDRA PUTRA (Society for Indonesian Biodiversity, 2024)
Abstract. Julian D, Reza M, Putra MGA. 2024. Length-weight relationship and condition factors of Lepturacanthus savala in Lampung Bay, Indonesia. Biodiversitas 25: 510-515. Scarce information exists regarding the growth aspects of ribbon fish (Lepturacanthus savala Cuvier, 1829) in Lampung Bay waters. Thus, this study aimed to analyze the growth characteristics as fundamental information for managing L. savala fishery resources in the waters of Lampung Bay. The method of this quantitative and descriptive study was to analyze the growth of L. savala. Length, weight, and sex ratio data were acquired through a purposive sampling method based on the catch results from gillnet landings at Lempasing Fishing Port, Bandar Lampung. A total of 347 specimens were collected during data collection from May to August 2023, with a length range between 21.6-59.8 cm of total length (TL) and the highest frequency observed in the length interval class of 33-36 cm, consisting of 105 specimens. The results showed that the growth pattern of L. savala is positively allometric, with a value of b equal to 3.0915. The sex ratio between males and females is 1:2.4. The condition factor values ranged from 0.0442 to 2.9281, with the highest average value observed in June for males and females, reaching 1.03.